Blockchain applications for secured and resilient supply chains: A systematic literature review and future research agenda. (January 2023) - Kumar Singh, Rajesh; Mishra, Ruchi; Gupta, Shivam; Mukherjee, Archana A.
Highlights: Significance of blockchain in developing a cyber-secure and resilient supply chain. Systematic review of 122 peer-reviewed papers published between 2012 and 2022. Six dominant themes related to behavioural factors for blockchain adoption. Theory, Methodology and Context (TMC) framework applied for future research. Abstract: Firms are using blockchain technology to prevent fraudulent activities through consensus mechanisms and help identify data tampering through its underlying characteristics, such as immutability, encryption transparency, and operational resilience. However, a holistic review of blockchain application in building a cyber-secure supply chain remains elusive, which can impede the advancement of the field when competing arguments are made, and pure replications are initiated. Therefore, the present study carries a systematic literature review to assess the state of literature review on the significance of blockchain in developing a cyber-secure and resilient supply chain. A systematic review of 122 peer-reviewed papers published between 2012 and 2022 has been conducted using a structured methodological approach. Further, the Theory, Context and Methodology (TCM) framework has been applied to suggest avenues for future research. Our analysis reveals six dominant themes related to blockchain and its adoption, blockchain application for resilience, blockchain application for cyber-security, blockchain and its role in intermediation, disintermediation and reintermediation, challenges of blockchain adoption and benefits of blockchain applications in the supply chain. Although the role of blockchain application in the cyber secure and resilient supply chain has been recognised, very little attention has been given to contextual factors affecting its adoption and consequences on key performance parameters. The present study contributes to the literature by synthesising the prime findings of reviewed papers and the managerial implications, thereby giving a holistic view of the existing research and presenting an array of future opportunities for firms to adopt blockchain technology in the supply chain.